Answer:
10
Step-by-step explanation:
We are going to substitute x = 3 - i into the expression x² - 6x
* Remember than i² = (√-1)² = -1. so when we multiply and get i² we're going to transform it into -1.*
⇒
Thus, x² - 6x = 10 when x = 3-i
______
We conclude that the frist trip takes 2.75 hours and the second one 2.5 hours.
Remember the relation:
Distance = Speed*Time.
Here the total distance of the trip is 55mi + 50mi = 105mi
And the total time is 5 hours and 15 minutes, remember that:
60 min = 1 hour
Then; 15 min = 0.25 hours.
So the total time is 5.25 hours, with that we conclude that the average speed is:
S = 105mi/5.25 h = 20 mi/h
The first trip is 55 miles long, then the time in which it is travelled is:
T = (55 mi)/(20 mi/h) = 2.75 hours
The second trip is 50 miles long, then:
T' = (50mi)/(20 mi/h) = 2.5 hours.
We conclude that the frist trip takes 2.75 hours and the second one 2.5 hours.
If you want to learn more about average speed:
#SPJ1
x + 60 inequality-lessthanorequalto 221; at most 161 pounds
x + 161 inequality-lessthanorequalto 221; at most 60 pounds
x + 60 inequality-lessthanorequalto 161; at most 221 pounds
Answer:
The answer would be 161
Step-by-step explanation:
D
3
- 1/3
-3
1/3